The State on the streets: police and politics in Argentina and Brazil - Hinton, Mercedes S. (Rienner, 2006)
Introduction: policing in Latin America -- Argentina -- The rise of insecurity -- Policing in the seat of power -- Reform the Argentine way -- Overriding threats and priorities? -- The Argentine political game -- Brazil -- The spillover of crime -- Policing the marvelous city -- Reform the Brazilian way -- Threats and priorities -- The Brazilian political game -- Conclusion -- Democratic policing: a distant reality? -- Methodological appendix -- List of acronyms and abbreviations.